Expert system for protection coordination of distribution system with distributed generators - Tuitemwong K. (2014)
Distributed or dispersed generation may cause various complexities to the operation of distribution system. Therefore, it is of interest to propose an expert system for protection coordination of distribution system under the presence of distributed generators. The expert system employs knowledge base and inference process to improve coordination settings of protective devices in order to accommodate the penetration of distributed generators. The expert system feeds input data by using graphical user interface and develops coordination settings based on power flow and short-circuit analyses. The expert system has been developed and successfully tested with a 22-kV distribution system with multiple distributed generations. © 2010 Elsevier Ltd. All rights reserved.